The use of TSI in designing a system for a university IS user support service. - Warren, Lorraine; Adman, Peter (Systems Research & Behavioral Science)
Part of a special issue on linking people, nature, business, and technology. The writers discuss the use of critical thinking systems in improving a university's information system (IS) user support service. They describe how total systems intervention (TSI) was employed to increase the efficiency and effectiveness of the IS user support service through deriving an improved design for that part of the service dealing with user requests, queries, and problems. They reveal how the use of the TSI informed the choice of the ETHICS methodology to carry out the design itself, and they reflect upon the usefulness of critical thinking systems in an IS management problem situation.